明末科擧與在野文人的互動 ──以金聖歎及其交遊爲案例 - 황위호; Wong Hugo Wai-ho (중국학보, 2019)
明代專以科擧取士，試以制義，旨在評騭士人書卷、辭理，以及闡發聖賢經傳本義的實力。迨至明末，制義趨於程文化及險僻怪戾，已與原意背道而馳。然而，不少士人依舊接受科擧制義的桎梏。究其原因，一方面，明代社會普遍推崇科擧，當時社會群體因而給予士人無形的壓力；另一方面，科擧制度本身將士人二分，考取擧人以上則擠身於官僚階級，是爲在位，否則爲在野。科擧制義幾乎成了士人擠身官僚階級的唯一通道，明末士人便希望考取科擧，以便得到社會身分的認同與自我價値的肯定。如是者，當時不少士人蠭然應擧，却又屢試不第，厭倦科場，最終淪爲在野文人。金聖歎（1608-1661）無疑是其中一個典型。金氏早歲多次應擧，甚至對於“生員”資格，竟然有補而旋棄，棄而旋補的反常行爲，最終仍爲一介生員。期間更與一些名不見經傳的在野文人交往。本文剖析金氏的應擧行爲及其背後的複雜心理，幷從金氏的交遊圈，開列當時其他在野文人的具體名單，以期達到以下三個目的：一，論證明末科擧對在野文人的影響；二，窺探明末科擧下在野文人的實際面貌；三，補苴金聖歎早期身世及交遊方面的硏究空白。 In Ming Dynasty, the Imperial Court selected the literates by testing their abilities on the knowledge, annotation and interpretation of the classical works, through the Examination Essays Sections in the Imperial Examination. The Essay writing section, in the late Ming dynasty in particular, is unable to align with the original objective of the Examination, i.e. to select the suitable calibres as the examination candidates. It is very common that the examinees strived to write the mechanical works as well as strange and brutal essays, which are difficult to be understood, during the examination. In addition, a number of literates apply for the Imperial examination because the society places a high value on the Imperial Examination. Another reason for the literates to apply for the Imperial Examination is that the literates are thirst to be renowned as “elite” in the hierarchy of society. Generally speaking, the literates can be catagorized into two different status in accord to their qualification in the examination system, and the cutting edge is whether they can obtain the “Juren” degree. For those who passed the examinations can be identified as “elite” in the social hierarchical ladder, because they have qualified a “license” to be civil servant. Whereas those who failed will be labeled as “general public”. In other words, taking the Imperial Examination and passing the Examination Essay Section are the only career path for the literates to be upgraded as the “elite” in the social hierarchical ladder during the Late Ming Dynasty. As a result, the literates tend to be the “elite” so as to be distinguished from the “general public” because it helps them to gain recognitions in terms of social status and self-esteem. In fact, most of the examinees still get failed in the Imperial examination for many years, who also feel exhausted and desperate under the continuous examinations. Thus, these literati can be labelled as “general public” or so-called “literates without honours”. JIN Shengtan as a typical example of “literates without honours”, he did attend the examinations for many times in his early age. This paper attempts to take JIN Shengtan as a case study and illustration to shed light on the relationship between Imperial Examination and “literates without honours” in the late Ming Dynasty. Besides, an analysis on JIN’s behavior and psychological struggles associated with the Imperial Examination will be discussed. To summarize, the paper tries to illustrate how the Imperial Examination influences the “literates without honours”, and to depict the full picture of literates’ activities under the examinations, and the social network at the early age of JIN Shengtan.